EFFECT OF BAKER'S YEAST CONCENTRATIONS ON ECO ENZYME PRODUCTS BY THE FERMENTATION PROCESS - Nurul Kamaliya; Cucuk Evi Lusiani (Politeknik Negeri Malang, 2023)
Eco enzyme is a liquid fermented from organic waste such as vegetable or fruit peels, brown sugar or molasses, water, and yeast. In the production of eco enzyme, yeast is used as a catalyst to accelerate the fermentation process, such as baker's yeast, one type of yeast that could be used. The purpose of this research is to determine how the concentration of baker's yeast affects the eco enzyme products. Citrus peels, melon peels, coconut brown sugar, water, and baker's yeast were ingredients used in this research. The eco enzyme fermentation process lasted ten days, after which the eco enzyme product was examined for pH value, acetic acid content, TDS (Total Dissolved Solids) value, organoleptic properties such as color and scent, and protease enzyme activity. The results showed that the value of pH value, acetic acid content, and TDS value increased as the concentration of baker's yeast was added in the production of eco enzyme. In this research, the range of pH values ​​was 4.15-4.2, acetic acid content was 1.35-2.03% v/v, TDS values was 1475-2056. Data from 25 panelists was used to generate color and scent from eco enzyme products. The test results showed that eco enzyme products had a fermented and citrus fruit scent and a pale yellow to deep yellow tint. Protease enzyme activity tests were performed on samples containing 5% % w/v baker's yeast, and it was discovered that there was one colony incubating for six days, but the results were not highly significant.